World Bank East Asia and Pacific Economic Update 2010, Volume 1 : Emerging Stronger from the Crisis - World Bank (World Bank, 2012)
East Asia has recovered from the economic and financial crisis. Largely thanks to China, the region's output, exports and employment have mostly returned to the levels before the crisis. Leading the global economy, real gross domestic product (GDP) growth in developing East Asia is poised to rise to 8.7 percent in 2010 after slowing from 8.5 percent in 2008 to 7.0 percent in 2009. This report also identifies two common regional agenda items for the medium term. First, the process of regional integration, driven by Association of South East Asian Nations (ASEAN) commitments to creating a single economic area, will need to continue. Deeper regional economic integration is now even more important, given prospects for slower growth in advanced economies. Behind-the-border trade barriers must be lowered, even in the face of incipient protectionist pressures around the world, including in the region. Deeper integration will encourage agglomeration economies and intra-industry trade, support sustainable urbanization, lower costs, and increase international competitiveness. Second, addressing climate change is high priority in the region. Mitigation measures must be strengthened to improve land and water use, bolster energy efficiency and conservation, and foster a much larger role for renewable sources of energy. Moreover, with investment rates in the region higher than in developed countries, there is scope for East Asia to move rapidly to the "green" technology frontier. Such a move will give the region a competitive advantage in a sector poised for rapid global growth. At the same time, the adaptation agenda will require enhancing the region's cooperation and disaster risk management frameworks. Institutional and regulatory frameworks for improving the resiliency of economic activity, reducing drought and flood risk, and managing coastal areas and small islands, are critically needed.